EFFECTIVENESS OF USING CANDLESTICK PATTERN AND DIVERGENCE ANALYSIS TECHNIQUES IN READING FOREX MARKET PRICE MOVEMENTS - Fajra Insani Kudadiri; Redy Herinanto Albertus; Junaidi Affan (Jurnal AKTUAL, 2022)
This study aims to determine the effectiveness of candlestick pattern signals and divergence signals in providing returns, and to compare the two signals in providing returns. The population in this study were the major currency pairs. The data used is secondary data taken from observations on forex market price movements from 2015 to 2019 totaling 100 data. Thestatistical tests used in this study are, the one sample t-test, and the independent t-test. The one sample t-test was used to test hypothesis 1 and hypothesis 2, while the independent t-test was used to test hypothesis 3. The results showed that: candlestick patterns in the majority of results show a positive and significance,  divergence in the majority of results shows a positive and significance, and comparison of divergences with candlestick patterns in the majority of results shows a negative and not significance. Based on the results of this study, the following conclusions are drawn: candlestick patterns are effective in providing returns, divergences are effective in providing returns, and candlestick patterns and divergences are no difference at providing returns.